The effect of competence, time budget pressure, and information technology on audit quality with independence as an intervening variable at the regional inspectorate office in Riau Islands Province - Faisal Faisal; Ngaliman Ngaliman; Muammar Khaddafi (LPPM STIE KRAKATAU, 2024)
Purpose: This study examines the influence between competence, time budget pressure, and information technology on audit quality with independence as an intervening variable at the Regional Inspectorate in Riau Islands Province. Research Methodology: The sample in this study were 122 people who worked as examiners at the Provincial and Regency / City Regional Inspectorates in Riau Islands Province using purposive sampling method. The data source of this research is primary data obtained from distributing questionnaires to research respondents. The data in this study were analyzed using the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach and using the smart PLS 3.0 analysis tool. Results: The results showed that each variable of competence, time budget pressure, and information technology and independence is related and has a positive effect on the quality of audits performed by auditors. The results showed that Competence, Time Budget Pressure, and Information Technology have a positive and significant effect on Audit Quality. Independence is able to mediate the influence between Competence, Time Budget Pressure, and Information Technology on Audit Quality.